The Role of a Ladderlike Communication Skill Course on Fostering Doctor-Patient Communication Competence of Students in Rural-oriented Free Tuition Medical Education Program - CHEN Enran, SHEN Ying, WEI Yuning, WEI Siyu (Zhongguo quanke yixue, 2024)
Background The phase of undergraduate medical education is the starting point for fostering communication competence of students in Rural-oriented Free Tuition Medical Education Program (RTME), which lays the foundation both for communication competence training in the postgraduate education phase and performing effective communications with patients and their relatives, colleagues, and other health personnel in the career life of general practitioners (GPs). It is of great practical significance to explore how to improve quality of doctor-patient communication education in the stage of undergraduate medical education and develop doctor-patient communication competence of the RTME students. Objective To explore the role of the ladderlike communication skill course on fostering doctor-patient communication competence of students in rural-oriented free tuition medical education program. Methods A total of 259 RTME students of Grade 2019 were selected from Guangxi Medical University in September 2019 to establish Cohort 1, and 262 undergraduate medical students of Grade 2019 were selected to establish Cohort 2. From September 2019 to January 2022, the students in Cohort 1 were trained in a ladderlike communication skill course lasting for five consecutive semesters; from September 2021 to January 2022, the students in both cohorts were trained in a doctor-patient communication course. The final exam scores and process assessment scores of the two cohorts on the doctor-patient communication course were compared and the evaluation of teaching effectiveness and satisfaction of ladderlike communication skill course were investigated in the students in Cohort 1. Results The RTME students achieved significantly greater total scores for the final exam of the doctor-patient communication course, in which the RTME students performed better on the sections of case analysis and small essay, but worse on the single-choice question section compared to the undergraduate medical students (P<0.05). Similarly, the RTME students obtained higher scores on the process assessment of the doctor-patient communication course than undergraduate medical students, resulting from higher scores on the dimensions of information collection, information giving, negotiation and resolution, and nonverbal communication skills (P<0.05), and there was no statistically significant difference in the scores on the dimension of establishing first impression (P>0.05). Over 80% of RTME students felt satisfied or absolutely satisfied with the content, pedagogical measures, faculty, schedule and effects of the ladderlike communication skill course, and more than 60% believed it helped or absolutely helped promote learning interest, increase confidence to encounter difficult patients, and raise multiple competence, including empathy, doctor-patient communication, language expression, problem resolution, and team work. Conclusion The ladderlike communication skill course significantly elevates the effects of doctor-patient communication education in the phase of undergraduate medical education for the RTME students, facilitates the development of doctor-patient communication competence and other comprehensive competence. The ladderlike course mode is an effective measure fostering doctor-patient communication competence of medical students in medical education, and makes a useful reference for communication competence training for postgraduate education and continuing education of general practice.